Aspek Hukum Sertifikat Hak Paten Sebagai Objek Jaminan Fidusia Menurut Undang - Undang Nomor 13 Tahun 2016 Tentang Paten - Putri Anggriani, Rica; Arifin Dilaga, Zaenal (Faculty of Law, University of Mataram, 2024)
This study aims to find out first how to bind patens as fiduciary guarantees and how to execute patents as fiduciary guarantees. The type of research used is normative research, with a statutory approach, conceptual approach, and historical approach. The results of the research show that the binding of patents rights as fiduciary guarantees can be used as fiduciary guarantees can be used as collateral objects by binding the paten rights to fiduciary guarantee institutions because patent rights are part of intellectual property rights where patent rights have economic principles that will provide economic benefits to the owner patents. Patents can be bound by fiduciary guarantees because patents are intangible movable objects included in the fiduciary guarantee category, the way to execute patents right in a written agreement because in general patents rights cannot be sold in public auctions, or sold on the securities trading market so that if execution is carried out by selling underhanded it will result in at transfer of patents rights wich is carried out in a written agreement in the form of a notarial deed and registered or recorded at the Directorate General of Intellectual Property Rights (Ditjen HAKI) and subject to administration fees.